Traditional Use, Phytochemical Profiles and Pharmacological Properties of Artemisia Genus from Central Asia - Aliya Nurlybekova; Aidana Kudaibergen; Aizhan Kazymbetova; Magzhan Amangeldi; Aizhamal Baiseitova; Meirambek Ospanov; Haji Akber Aisa; Yang Ye; Mohamed Ali Ibrahim; Janar Jenis (Molecules, 2022)
The flora of Kazakhstan is characterized by its wide variety of different types of medicinal plants, many of which can be used on an industrial scale. The Traditional Kazakh Medicine (TKM) was developed during centuries based on the six elements of ancient Kazakh theory, associating different fields such as pharmacology, anatomy, pathology, immunology and food nursing as well as disease prevention. The endemic Artemisia L. species are potential sources of unique and new natural products and new chemical structures, displaying diverse bioactivities and leading to the development of safe and effective phytomedicines against prevailing diseases in Kazakhstan and the Central Asia region. This review provides an overview of Artemisia species from Central Asia, particularly traditional uses in folk medicine and the recent numerous phytochemical and pharmacological studies. The review is done by the methods of literature searches in well-known scientific websites (Scifinder and Pubmed) and data collection in university libraries. Furthermore, our aim is to search for promising and potentially active Artemisia species candidates, encouraging us to analyze Protein Tyrosine Phosphatase 1B (PTP1B), α-glucosidase and bacterial neuraminidase (BNA) inhibition as well as the antioxidant potentials of Artemisia plant extracts, in which endemic species have not been explored for their secondary metabolites and biological activities so far. The main result of the study was that, for the first time, the species Artemisia scopiformis Ledeb. Artemisia albicerata Krasch., Artemisia transiliensis Poljakov, Artemisia schrenkiana Ledeb., Artemisia nitrosa Weber and Artemisia albida Willd. ex Ledeb. due to their special metabolites, showed a high potential for α-glucosidase, PTP1B and BNA inhibition, which is associated with diabetes, obesity and bacterial infections. In addition, we revealed that the methanol extracts of Artemisia were a potent source of polyphenolic compounds. The total polyphenolic contents of Artemisia extracts were correlated with antioxidant potential and varied according to plant origin, the solvent of extraction and the analytical method used. Consequently, oxidative stress caused by reactive oxygen species (ROS) may be managed by the dietary intake of current Artemisia species. The antioxidant potentials of the species A. schrenkiana, A. scopaeformis, A. transiliensis and Artemisia scoparia Waldst. & Kitam. were also promising. In conclusion, the examination of details between different Artemisia species in our research has shown that plant materials are good as an antioxidant and eznyme inhibitory functional natural source.